Fantastyka i temat Holokaustu. Między wątpliwościami a funkcjonalnością konwencji fantastycznych - Brzóstowicz-Klajn, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Starting with Jerzy Jarzębski’s opinion that the fantastic convention in contemporary literature fulfills the role of “artificial sense”, the Author analyzes selected works related to the subject of the Holocaust in order to check the functionality and artistic value of fantastic elements used there. She notes that fantasy helps writers express the experience of emptiness following a loss, strengthens the trauma related to the past, and emphasizes the literariness of the text, fulfilling the role of metafiction.